A‐Site Management for Highly Crystalline Perovskites. Issue 4 (11th November 2019) - Si, Haonan; Zhang, Zheng; Liao, Qingliang; Zhang, Guangjie; Ou, Yang; Zhang, Suicai; Wu, Hualin; Wu, Jing; Kang, Zhuo; Zhang, Yue
Abstract: An in‐depth understanding and effective suppression of nonradiative recombination pathways in perovskites are crucial to their crystallization process, in which supersaturation discrepancies at different time scales between CH3 NH3 I (MAI, methylammonium iodide) and PbI2 remain a key issue. Here, an A‐site management strategy via the introduction of an A‐site placeholder cation, NH4 +, to offset the deficient MA + precipitation by occupying the cavity of Pb–I framework, is proposed. The temporarily remaining NH4 + is substituted by subsequently precipitated MA + . The temperature‐dependent crystallization process with the generation and consumption of a transient phase is sufficiently demonstrated by the dynamic changes in crystal structure characteristic peaks through in situ grazing‐incidence X‐ray diffraction and the surface potential difference evolution through temperature‐dependent Kelvin probe force microscopy. A highly crystalline perovskite is consequently acquired, indicated by the enlarged grain size, lowered nonradiative defect density, prolonged carrier lifetime, and fluorescence lifetime imaging. Most importantly, it is identified that the A‐site IMA defect is responsible for such crystal quality optimization based on theoretical calculations, transient absorption, and deep‐level transient spectroscopy. Furthermore, the universality of the proposed A‐site management strategy is demonstrated with other mixed‐cation perovskite systems, indicating that this methodology successfully provides guidance for synthesis route design of highly crystalline perovskites. Abstract : A‐site management by introducing an A‐site placeholder cation, NH4 +, during the perovskite crystallization process is proposed to balance the supersaturation discrepancy between AX and BX2 so as to improve its crystal quality without any residue. Most importantly, the sharply decreased A‐site‐related defect IMA indicates that it is responsible for such crystalline optimization.